Cyberbullying and Thai Generation Z Youths in Bangkok, Thailand - Euajarusphan, Adipon (Asian Crime and Society Review, 2021)
This research has the objective to study the behavior of using online media, awareness, attitudes, and intentions that lead to cyberbullying among Thai Generation Z youths. This includes the attitude towards handling cyberbullying and the relationship between awareness, attitude, and cyberbullying intention and the attitude towards handling cyberbullying of Thai Generation Z youths. The study is quantitative research, utilizing a questionnaire for data collection from 400 Thai youths aged between 19-24 years in Bangkok. The statistical analysis included percentage, mean, standard deviation, t-test, F-test, One-way ANOVA, LSD, and Pearson’s Correlation Coefficient. The analysis of personal factors at the significance level of 0.05 indicated that gender has an impact on online media usage, location of online media usage, and time of online media use are statistically different. Age has an impact on online media usage, location of online media usage, time of online media use, online social media network used, and reason for using online social media are statistically different. Education level has an impact on online media usage, and the location, time, and online social media network used are statistically different. In addition, the analysis of cyberbullying experience revealed that most of the respondents have experienced cyberbullying, awareness about cyberbullying behavior and a negative attitude towards cyberbullying at a high level. Regarding cyberbullying intention, the respondents are highly unlikely to engage in such behaviors. The respondents reported that they are highly capable of handling cyberbullying behavior. Examination of the relationship between awareness, attitude, and cyberbullying intention and the attitude in handling cyberbullying of Thai youths in Generation Z found that awareness of cyberbullying has a relationship with attitude in handling cyberbullying is quite low. The relationship between cyberbullying intention and attitude in handling cyberbullying is quite low.